Avaliação de biomarcadores de efeito e metabolômica com modulação da microbiota intestinal na exposição subcrônica de camundongos C57bl/6 à mistura de agrotóxicos: glifosato, imidacloprido e tebuconazol. - Mirna Maciel d'Auriol Souza (2024)
Pesticides are considered endocrine disruptors and, with chronic exposure, can trigger metabolic diseases such as obesity and diabetes mellitus. Exposure to these compounds is usually oral through the ingestion of food. The first contact with the body is through the gastrointestinal tract and, consequently, the gut microbiota, which, when affected, leads to dysbiosis. The aim of this study was to evaluate the subchronic exposure to a mixture of pesticides (imidacloprid, tebuconazole, and glyphosate) at low doses through genotoxicity and untargeted metabolomics studies and the impact on the microbiota with modulation by the probiotic Bifidobacterium longum 51A. For this, four groups of animals were used: Control (CTRL); Mixture (AGT); Probiotic (PROB); and Mixture and Probiotic (AGT+PROB). The parameters evaluated were: body weight; relative weight of organs (liver, spleen, kidneys, and periuterine adipose tissue); fasting glucose; insulin sensitivity; total cholesterol and serum triglycerides; oxidative stress (lipid peroxidation and superoxide dismutase activity); myeloperoxidase (MPO) activity evaluation; histopathological evaluation (spleen, large intestine, and kidneys); gut microbiota; short-chain fatty acid (SCFA) production (acetate and butyrate); micronucleus test; and untargeted metabolomics analysis. Exposure to pesticides at low doses did not alter body weight, relative weight of organs, or histopathology but caused an increase in total cholesterol, a decrease in serum triglycerides and insulin sensitivity, without altering fasting glucose in the animals; decreased MPO activity in the spleen; and showed a genotoxic effect, increasing the frequency of micronuclei (MN) in the peripheral blood of the animals. The modulation of the gut microbiota with B. longum 51A, despite the mixture having harmed SCFA production of the bacteria by decreasing acetate and butyrate production, helped exposed animals reduce lipid peroxidation and, consequently, oxidative stress, via an independent pathway of SCFA production. Untargeted metabolomics analysis by gas chromatography-mass spectrometry identified that the pesticide mixture produced toxicity through multiple mechanisms, but mainly through oxidative stress, affecting the energy metabolism of exposed animals by altering the tricarboxylic acid cycle, galactose metabolism, glyoxylate pathway, and carboxylic acid biosynthesis, confirming alterations in total cholesterol, triglycerides, and insulin sensitivity. The probiotic B. longum 51A managed to reverse the damage caused by oxidative stress from the pesticide mixture, as seen in the metabolomics analysis by the reduction of metabolites such as glutamine, malic acid, gluconic acid, and 2-hydroxybutyric acid. Thus, it is suggested that modulation by B. longum 51A optimized the carbohydrate/energy metabolism of the animals, balancing anabolic and catabolic reactions and controlling the pentose phosphate and NADPH pathways, alleviating oxidative stress. The data from this study suggest the mixture of imidacloprid, tebuconazole, and glyphosate pesticides, at low doses and for a subchronic period, is an endocrine disruptor, affecting the gut microbiota and causing dysbiosis, and causing oxidative stress, which leads to alterations in total cholesterol, serum triglycerides, and insulin sensitivity. These results also suggest the gut microbiota can be used as a biomarker of susceptibility to environmental exposure to pesticides at low doses.